Perceived motivational climate and goal orientation in soccer athletes: A longitudinal perspektive - Domingues, M. (Journal of Human Sport & Exercise, 2019)
The study aims to understand the differences in motivation to help individuals, independently of their abilities to reach their full potential. The central point aims to study behaviour variability more than predicting performance outcomes. The purpose of the study was to characterize the clubs motivational climate and goal achievement regarding their coaches and athletes and to analyse the effects of time and context in these variables. We also intended to examine the variation in results associated with the training environment of latent variables resulting from the TEOSQ and PMCSQ. We will sample 120 football youngsters with ages 12-18 years old, coaches of each team with a longitudinal perspective. To assess the problem we will apply two questionnaires (TEOSQ and PMCSQ) with descriptive statistics and t-test and we also carried out analysis of content. There is a relationship between the approach undertaken by the coach and the sport context and the motivational climate variables.